Exploring the Use of Flashcards in Teaching English Vocabulary at Ban Buketamong School, Thailand - Nabil, Muhammad; Qomariyah, Dewi Nurul (Critical Review of English-Arabic World Journal, 2025)
Teaching vocabulary plays a fundamental role in English language learning, particularly in contexts where English is taught as a foreign language. Many students still experience difficulties in understanding and remembering English vocabulary due to limited exposure and low learning motivation. Therefore, teachers are required to use appropriate and engaging learning media to support vocabulary learning. Flashcards are visual learning media that can help students understand word meanings more easily and increase their participation in the classroom. This research aims to explore the use of flashcards in teaching English vocabulary at Ban Buketamong School, Narathiwat, Thailand. This study employed a descriptive qualitative research design involving one English teacher and 19 eighth grade students. The data were collected through classroom observations, interviews, and document review. To ensure data validity, source triangulation and technique triangulation were applied. The findings showed that the teacher planned flashcard based instruction by preparing lesson plans, selecting relevant vocabulary materials, designing teacher made laminated flashcards, and organizing learning activities. The implementation emphasized clear learning goals, vocabulary related to daily activities and nature, and systematic procedures including introduction, practice, and review stages. Evaluation was conducted through formative assessment during classroom interaction and summative assessment using picture based quizzes.